Mapping of the Inferior Glenohumeral Ligament for Suture Pullout Strength: A Biomechanical Analysis. Issue 1 (8th January 2021) - Raniga, Sumit; Cadman, Joseph; Dabirrahmani, Danè; Bui, David; Appleyard, Richard; Bokor, Desmond
Background: Suture pullout during rehabilitation may result in loss of tension in the inferior glenohumeral ligament (IGHL) and contribute to recurrent instability after capsular plication, performed with or without labral repair. To date, the suture pullout strength in the IGHL is not well-documented. This may contribute to recurrent instability. Purpose/Hypothesis: A cadaveric biomechanical study was designed to investigate the suture pullout strength of sutures in the IGHL. We hypothesized that there would be no significant variability of suture pullout strength between specimens and zones. Additionally, we sought to determine the impact of early mobilization on sutures in the IGHL at time zero. We hypothesized that capsular plication sutures would fail under low load. Study Design: Descriptive laboratory study. Methods: Seven fresh-frozen cadaveric shoulders were dissected to isolate the IGHL complex, which was then divided into 18 zones. Sutures in these zones were attached to a linear actuator, and the resistance to suture pullout was recorded. A suture pullout strength map of the IGHL was constructed. These loads were used to calculate the load applied at the hand that would initiate suture pullout in the IGHL. Results: Mean suture pullout strength for all specimens was 61.6 ± 26.1 N. The maximum load found to cause suture pullout through tissue was found to be low, regardless of zone of the IGHL. Calculations suggest that an external rotation force applied to the hand of only 9.6 N may be sufficient to tear capsular sutures at time zero. Conclusion: This study did not provide clear evidence of desirable locations for fixation in the IGHL. However, given the low magnitude of failure loads, the results suggest the timetable for initiation of range-of-motion exercises should be reconsidered to prevent suture pullout through the IGHL. Clinical Relevance: From this biomechanical study, the magnitude of force required to cause suture pullout through the IGHL is met or surpassed by normal postoperative early range-of-motion protocols.